Systematic characterization of extracellular vesicles from potato (Solanum tuberosum cv. Laura) roots and peels: biophysical properties and proteomic profiling - Ekanayake, Gayandi; Piibor, Johanna; Midekessa, Getnet; Godakumara, Kasun; Dissanayake, Keerthie; Andronowska, Aneta; Bhat, Rajeev; Fazeli, Alireza (Frontiers in Plant Science, 2024)
Extracellular vesicles (EVs) facilitate inter and intra-species/kingdom communication through biomolecule transfer, including proteins and small RNAs. Plant derived EVs, a hot topic in the field, hold immense potential both as a potential biomarker to study plant physiology and as a biomaterial that can be mass-produced to be used in various industries ranging from cosmetics and food additives to biological pesticides. A systematic characterization of EVs is required as a foundation for further investigations. In the current study, we enriched vesicles from hydroponically cultivated potato plants (Solanum tuberosum, cv. Laura), isolating root exudates and apoplastic wash from potato peels via vacuum infiltration. We have then attempted to systematically characterize the enriched EVs to investigate their similarity to standard characteristics of EVs and their potential roles in plant physiology. Biophysical and chemical analyses unveiled morphological similarities between EVs from potato roots and peels. The diameter of EVs from potato roots (164.6 ± 7.3 nm) was significantly larger than those from peels (132.2 ± 2.0 nm, p < 0.004). Liquid chromatography-mass spectrometry (LC-MS) showed substantial protein enrichment in purified EVs compared to crude samples from both sources (42% and 25% enrichment of root EVs and peel EVs respectively). Only 11.8% of identified proteins were common, with merely 2% significantly enriched proteins shared between potato root and peel EVs. Pathways associated with responses to biotic and abiotic stress factors were significantly enriched in potato peel and root EV proteomes, hinting at a defensive role played by EVs in plants. With further experimentation to elucidate the specific methods of communications, these findings increase the details known about plant EVs in terms of their physical and chemical character and their potential functions, aiding in sustainable agricultural waste utilization for large-scale EV production, aligning with "valorization.